2020
DOI: 10.1002/bmc.4910
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for qualitative and quantitative profiling of Angelicae Pubescentis Radix and detection of its analgesic and anti‐inflammatory components by spectrum–effect relationship and multivariate statistical analysis

Abstract: This study established a spectrum–effect relationship method for screening and quantifying the analgesic and anti‐inflammatory active ingredients in Angelicae Pubescentis Radix (AP) by ultra‐high‐performance liquid chromatography–quadrupole mass spectrometry detector analysis (UPLC–QDA). First, the fingerprint of AP was established to determine the common peaks. Next, six batches of AP samples, with significant differences, were selected for evaluation of pharmacological activity. Subsequently, the spectrum–ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The gray correlation analysis method can significantly reduce the bias caused by information asymmetry, hence, it was widely used to investigate the correlation degree between two sets of variations with a relatively simple calculation way ( Hou et al, 2020 ; Ren, et al, 2020 ). The gray correlation degree was calculated by Excel functions and its data analysis tool.…”
Section: Methodsmentioning
confidence: 99%
“…The gray correlation analysis method can significantly reduce the bias caused by information asymmetry, hence, it was widely used to investigate the correlation degree between two sets of variations with a relatively simple calculation way ( Hou et al, 2020 ; Ren, et al, 2020 ). The gray correlation degree was calculated by Excel functions and its data analysis tool.…”
Section: Methodsmentioning
confidence: 99%
“…The decoction of AP has sedative and hypnotic effects on rats and mice and can prevent the convulsive effect of strychnine on frogs but it cannot prevent them from dying. Li et al studied the anti-inflammatory effect of the AP ethanol extract of different concentrations on cotton ball implantation and found that 60% and 80% ethanol extract had anti-inflammatory effect ( P < 0.05), while 40% ethanol extract had no such effect [ 93 ]. The fingerprint-effect relationship of AP was established by Hou et al, whose research results showed that the extract of AP had significant inhibitory effects on the pain and inflammatory reactions of mice caused by hot plate ( P < 0.01), acetic acid writhing ( P < 0.01, the analgesia rate could reach 89.27%), formalin ( P < 0.01, the analgesia rate could reach 52.91%), ear swelling ( P < 0.01, the inhibition rate of swelling was up to 69.33%), caused by xylene, and foot swelling ( P < 0.01, the inhibition rate of inflammation was 23.49%), caused by carrageenan.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…As a traditional Chinese medicine, AP has a variety of effects, such as anti-inflammatory [93], anti-rheumatism, sedation Evidence-Based Complementary and Alternative Medicine [94], hypnosis, neuroprotection [95], antioxidation [96], antitumor [97], and antigastric ulcer [98], which has been studied and confirmed by many scholars. At present, the pharmacological effects of AP are summarized in Table 5, which is described in detail as follows.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…CE can be absorbed by colon cancer cells by passive diffusion. In animal experiments, intestinal epithelial cells can be well absorbed and fully distributed in peripheral blood by oral administration (Yang et al, 2008;Hou et al, 2020;Ge et al, 2019;Yang et al, 2019). So far, although there are few reports on the specific effects of CE on tumors, the above-discussed studies have shown that CE is easy to metabolize and has anti-inflammatory effects, which may be more helpful in treating tumor diseases.…”
Section: Introductionmentioning
confidence: 99%